Components of future social workers' readiness to implement mediation - Badziun Oksana Yevgeniivna, Kulinchenko Oleksandr Sergiyovych, (Opción, 2019)
The objective of this article is to review the theoretical background, to develop components of future social workers’ readiness to implement mediation in their practice and study to what extent this competence is developed via different diagnostic techniques like Diagnostics of One’s Proneness to Conflict Behavior. The study results demonstrate that a significant proportion of students (28.8%) are highly motivated to study the principles of peacebuilding and implementation of mediation practice, and 25.5% have well-developed qualities required for a mediator. In conclusion, the process of building the future social workers’ readiness to implement mediation requires a step-by-step approach.